ANALISIS PERMINTAAN UANG PADA MASYARAKAT ISLAM KONTEMPORER - Ziecky Mardoni (Bajang Institute, 2022)
This study aims to analyze and determine the effect of interest rates and GDP on the demand for money in contemporary Islamic society. This type of research is descriptive and associative. While the type of data is documentary data, the data source is secondary data and time series data from the first quarter of 2015 to the fourth quarter of 2018. The analysis tool is a simultaneous equation model using the Two Stages Least Squared (TSLS) method. The results of the study conclude that the existing estimates explain that interest rates do not have a significant effect on the demand for money. This fact supports the initial hypothesis which states that there is no effect of interest rates in motivating a contemporary society to hold money in Indonesia. What has a significant effect on the demand for real money based on estimates, is that the level of income in accordance with the theory of income levels will have a positive effect on the demand for money. Based on the results of the research conducted, suggestions can be given, namely, even though the results show that there is no significant relationship between the interest rate and the demand for money, it is not necessarily the insignificant effect of the interest rate because most Indonesian people embrace Islam and have good awareness. against the prohibition of interest, but it could also be due to the high rate of profit sharing from Islamic banks. So that there is no such public attitude, we still need to promote Islamic banking products, and a good explanation about the prohibition of interest. In addition, the improvement of Islamic banking services is also very important in this regard.